2022
DOI: 10.3390/pharmaceutics14050908
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Derived from Dental Pulp Stem Cells Show Different Angiogenic and Osteogenic Properties in Relation to the Age of the Donor

Abstract: Craniofacial tissue reconstruction still represents a challenge in regenerative medicine. Mesenchymal stem cell (MSC)-based tissue engineering strategies have been introduced to enhance bone tissue repair. However, the risk of related complications is limiting their usage. To overcome these drawbacks, exosomes (EXOs) derived from MSCs have been recently proposed as a cell-free alternative to MSCs to direct tissue regeneration. It was hypothesized that there is a correlation between the biological properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Therefore, prompt treatment and effective rehabilitation strategy are of great significance to reduce the heavy social burdens . The key barrier in SCI treatment is the hostile microenvironment which includes neuronal loss, oxidation stress, inflammation, and glial scar deposition. , It was reported that exosomes derived from mesenchymal stem cells (MSC-Exo) exhibited great potential in treating SCI and other diseases through regulating the inhibitory microenvironment. However, the conventional methods for harvesting therapeutic exosomes are mainly based on two-dimensional (2D) culture technology where mesenchymal stem cells (MSCs) adhere on substrate as a monolayer. Unfortunately, 2D culture mode cannot mimic the exact physilogical conditions of MSCs niche and this severely limits the therapeutic potency of exosomes in clinical application .…”
mentioning
confidence: 99%
“…Therefore, prompt treatment and effective rehabilitation strategy are of great significance to reduce the heavy social burdens . The key barrier in SCI treatment is the hostile microenvironment which includes neuronal loss, oxidation stress, inflammation, and glial scar deposition. , It was reported that exosomes derived from mesenchymal stem cells (MSC-Exo) exhibited great potential in treating SCI and other diseases through regulating the inhibitory microenvironment. However, the conventional methods for harvesting therapeutic exosomes are mainly based on two-dimensional (2D) culture technology where mesenchymal stem cells (MSCs) adhere on substrate as a monolayer. Unfortunately, 2D culture mode cannot mimic the exact physilogical conditions of MSCs niche and this severely limits the therapeutic potency of exosomes in clinical application .…”
mentioning
confidence: 99%
“…Moreover, the previously conducted studies detected the following contents [33,34], macrophage colony-stimulating factor (M-CSF), monocyte chemotactic protein-1 (MCP-1), interleukin 1 receptor antagonist (IL-1ra), and stromal cell-derived factor 1-alpha (SDF-1a), in addition to the angiogenic factors such as vascular endothelial growth factor (VEGF), hepatocyte growth factor (HGF), and basic fibroblast growth factor (b-FGF). Furthermore, the detected miRNAs in the DPSCs derived exosomes were miR-22, miR-27a, miR-30b-5p, miR-324-5p, miR-130a-3p, miR-34a-5p, miR-378f, miR-513b-5p, miR-193a-5p, miR-5100, miR-4792, miR-652-3p miR-505-3p, miR-27a-5p miR-629-5p, miR-1260b, miR-140-3p,…”
Section: Isolation and Characterization Of Dpscs And Dpscs-exosomesmentioning
confidence: 95%
“…In literature, it is reported that the exposure to a magnetic field is able to favor the anti-inflammatory molecular pathways and can also decrease the production of the ROS [ 14 ] in many cellular models. It is well accepted that the devices committed to producing magnetic fields (EMF) are able to affect numerous biological processes, including wound and bone healing, inflammation, osteoarthritis, post-operative edema, chronic/neuropathy pain and tissue repair [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. To ensure safe exposures, exposure guidelines have been regularly developed and revised based on the available scientific knowledge such as the “exposure guidelines” that are published by the International Commission on Non-Ionizing Radiation Protection (ICNIRP).…”
Section: Introductionmentioning
confidence: 99%